2010
DOI: 10.1111/j.1365-2141.2010.08246.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in adult acute lymphoblastic leukaemia

Abstract: SummaryTreatment of acute lymphoblastic leukaemia (ALL) in adults presents a formidable challenge. While overall results have improved over the past 3 decades, the long-term survival for patients aged less than 60 years is only in the range of 30-40% and is 10-15% if between 60 and 70 years and <5% for those over 70 years. The historic lack of clear-cut biological prognostic factors has led to over-or under-treatment of some patients. Response to initial therapy is an important prognosticator of outcome based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 118 publications
(139 reference statements)
3
72
0
2
Order By: Relevance
“…A cutoff value of 30 Â 10 9 /L has often been used in clinical studies of B-cell ALL and its significance has been shown in previous reports. 3,17 Marks reported that a WBC 425 Â 10 9 /L at diagnosis predicted a worse outcome for adult patients with ALL in CR1/2 who received Fludarabine-containing RIST for elderly B-ALL H Kanamori et al transplantation after either full conditioning (n ¼ 1421) or reduced-intensity conditioning (n ¼ 92). 14 However, there has been no report about the clinical impact of WBC at diagnosis on survival among patients receiving RIST alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cutoff value of 30 Â 10 9 /L has often been used in clinical studies of B-cell ALL and its significance has been shown in previous reports. 3,17 Marks reported that a WBC 425 Â 10 9 /L at diagnosis predicted a worse outcome for adult patients with ALL in CR1/2 who received Fludarabine-containing RIST for elderly B-ALL H Kanamori et al transplantation after either full conditioning (n ¼ 1421) or reduced-intensity conditioning (n ¼ 92). 14 However, there has been no report about the clinical impact of WBC at diagnosis on survival among patients receiving RIST alone.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, factors such as age, immunophenotype, WBC and cytogenetic abnormalities are associated with the outcome of chemotherapy and/or transplantation for ALL. 17 The Ph chromosome is the most frequent and clinically significant abnormality in adult ALL, with an incidence ranging from 15 to 50% among older patients with B-cell ALL. 18 Use of tyrosine kinase inhibitors combined with chemotherapy has altered the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Adults with ALL, on the other hand, still have a very poor prognosis; the long-term survival rate for adult cases is a mere 30-40% and decreases with age. 2,3 Studies have shown that younger adults treated on pediatric protocols have an increased overall survival compared with those on adult protocols. 4,5 However, it should be emphasized that adult ALL differs significantly from pediatric ALL as regards complete remission rates, minimal residual disease response level and risk group assignments, even when treated on pediatric protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In childhood ALL, males tended to have a worse overall prognosis than females did, 19,42 although that difference was not as clear in adult ALL. 43 In AML, males fared worse than females did. 44,45 Strong recommendation for testing for KIT mutation in adult patients with CBF-AML Expert consensus opinion for testing for KIT mutation in pediatric patients with CBF-AML 18.…”
Section: Strong Recommendationmentioning
confidence: 99%